2018
DOI: 10.1007/s11266-018-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering and Wellbeing Among Ageing Adults: A Longitudinal Analysis

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 75 publications
5
36
0
Order By: Relevance
“…A longitudinal study for retired men and women revealed that the frequency of volunteering, as well as future intentions to perform such activities, predicted higher positive affect in the feeling of ability (Pushkar et al, 2010). One of the scarce studies with panel data found positive evidence for the moderating influence of volunteering on the relationship between negative self-esteem and wellbeing (Russell et al, 2019). The results of these articles suggest that volunteering might act as a safeguard for seniors.…”
Section: Literature Reviewmentioning
confidence: 98%
“…A longitudinal study for retired men and women revealed that the frequency of volunteering, as well as future intentions to perform such activities, predicted higher positive affect in the feeling of ability (Pushkar et al, 2010). One of the scarce studies with panel data found positive evidence for the moderating influence of volunteering on the relationship between negative self-esteem and wellbeing (Russell et al, 2019). The results of these articles suggest that volunteering might act as a safeguard for seniors.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, hardly any research has considered neighborhood belonging as an outcome. Voluntary participation may foster neighborhood belonging because it often occurs at the community level and may attach people to places and communities (Berkman et al, 2000;Russell et al, 2019). In a meta-analysis, Talò et al (2014) found an average correlation of 0.36 between voluntary participation and sense of community, a psychological construct that encompasses feelings of belongingness to, mattering in, and being emotionally connected to a community (McMillan & Chavis, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…However, research has shown that people are motivated to volunteer also to grow and satisfy personal psychological needs [ 6 , 7 , 8 ]. Evidence exists that volunteering may promote the volunteers’ benefits in terms of physical, social, and psychological health [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Most studies have focused only on the beneficial effects of engaging in volunteering, whereas individual characteristics that may contribute to volunteers’ psychological health have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%